Republic of Latvia : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation with Republic of Latvia highlights that the economy continued to expand rapidly in 2018, as growth surprised with a strong construction-driven upswing. Fiscal and current account deficits are at manageable levels, as is the public debt. The financial system remains stable, despite a significant balance sheet restructuring of banks servicing foreign clients. The growth outlook is favourable; however, risks weigh on the downside due to a less supportive external environment. The financial system remains stable despite a significant balance sheet restructuring of banks servicing foreign clients. Banks remains well capitalized and liquid, with capital levels about 40 percent higher than the euro area average and average liquidity coverage four times the regulatory minimum. Higher productivity and investment growth are needed to offset the impact of Latvia's exceptionally unfavorable demographic trends and achieve robust long-term growth and rapid income convergence.